DISEMINASI KOMUNIKASI DAKWAH PADA KOMPETENSI KEWIRAUSAHAAN ANGKATAN KERJA - Usman, Usman; Syamsidar, Syamsidar (Komodifikasi, 2019)
This research discusses three things. 1) the characteristics of the system (process and structure) in the inheritance of knowledge, skills and values in improving the entrepreneurial competence of the workforce; 2) the possibility of wide application in the interests of developing labor competencies (in Bulukumba Regency) 3) influential factors in question include: the potential of LW, workforce personality, leadership skills, availability of raw materials. 3) Entrepreneurial competencies include: skills to recognize and use production tools, skills to choose and recognize raw materials that are suitable for making or producing something, making something that is marketable as a source of livelihood, making according to the tastes of buyers and business management skills. The object of research is Phinisi boat workers in Bulukumba. As a result, the process of applying the dakwah model in LW is: the courtier (coach) gives an explanation, examples, and duties of mustard listening, seeing and paying attention, then he does something according to the explanation heard by imitating the example he sees. The effectiveness of the Dakwah LW model in enhancing the entrepreneurial attitudes of the workforce in Bonto Bahari Sub-district, Bulukumba Regency, can be seen from the special characteristics of LW as a forum for labor development: (1) fostering workforce learning workforce (workforce-work skills through work processes), (2) the results in the form of production skills make mustard must not depend on the availability of employment because they have their own jobs, and (3) the sign (token) is not a diploma, but the skills of production.